2010
DOI: 10.1289/ehp.0901418
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of the Herbicide Atrazine Alter Sex Ratios and Reduce Metamorphic Success in Rana pipiens Tadpoles Raised in Outdoor Mesocosms

Abstract: BackgroundThere are conflicting reports regarding the effects of atrazine (ATZ) on amphibian development. Therefore, further studies are needed to examine the potential mechanisms of action of ATZ in amphibians.ObjectivesOur aim in this study was to determine whether low concentrations of ATZ affect gonadal development and metamorphosis in the Northern leopard frog, Rana pipiens.MethodsTadpoles were exposed in outdoor mesocosms to nominal concentrations of 0.1 and 1.8 μg/L of formulated ATZ from Gosner stage 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
48
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 51 publications
7
48
1
Order By: Relevance
“…Furthermore, we showed that feminization is persistent and complete, resulting in reproductively functional females capable of producing viable eggs. Together, the present data and these three similar reports (5,39,40) suggest that sex-reversal by atrazine (complete feminization of genetic males) is not a species-specific effect but rather one that occurs across nonamniote vertebrate classes.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, we showed that feminization is persistent and complete, resulting in reproductively functional females capable of producing viable eggs. Together, the present data and these three similar reports (5,39,40) suggest that sex-reversal by atrazine (complete feminization of genetic males) is not a species-specific effect but rather one that occurs across nonamniote vertebrate classes.…”
Section: Discussionsupporting
confidence: 83%
“…This result, coupled with studies illustrating that amphibian sex differentiation is sensitive to estrogen exposure in the laboratory (8,12,15,16), challenges the assumption that amphibian sex determination is strictly genetic (14) and implies a potential role for environmental sex modification. Offspring sex ratio is generally poorly studied in metamorphosing amphibians from wild populations, though it is commonly understood that amphibians have genetic sex determination (14).…”
Section: Discussionmentioning
confidence: 96%
“…Offspring sex ratio is generally poorly studied in metamorphosing amphibians from wild populations, though it is commonly understood that amphibians have genetic sex determination (14). Although laboratory studies indicate that amphibian sex ratios can be environmentally manipulated (8,12), these prior results provide no indication of normal sex ratio variation in wild populations from different environments. Limited evidence from a single natural frog population indicates that normal metamorph sex ratios can sometimes be skewed toward one sex (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations